Sigmatineurum puleloai (Diptera: Dolichopodidae), a new species from Pelekunu Stream, Moloka’i, Hawaiian Islands - Englund, R. A.; Evenhuis, N. L. (Zootaxa, 2005)
Sigmatineurum puleloai, sp. nov. from the island of Moloka‘i in the Hawaiian Islands is described and illustrated. It is characterized by strong bristles on the middle ventral section of the midleg femur, flattened sternite 4 process, and conspicuous dark pollinose areas on the dorsolateral portions of the abdominal tergites.